Codon usage analysis of zoonotic coronaviruses reveals lower adaptation to humans by SARS-CoV-2 - Huang, Wanyi (Infect Genet Evol, 2021)
Since 2002, the world has witnessed major outbreaks of acute respiratory illness by three zoonotic coronaviruses (CoVs), which differ from each other in pathogenicity. Reasons for the lower pathogenicity of SARS-CoV-2 than the other two zoonotic coronaviruses, SARS-CoV and MERS-CoV, are not well understood. We herein compared the codon usage patterns of the three zoonotic CoVs causing severe acute respiratory syndromes and four human-specific CoVs (NL63, 229E, OC43, and HKU1) causing mild diseases. We found that the seven viruses have different codon usages, with SARS-CoV-2 having the lowest effective number of codons (ENC) among the zoonotic CoVs. Human codon adaptation index (CAI) analysis revealed that the CAI value of SARS-CoV-2 is the lowest among the zoonotic CoVs. The ENC and CAI values of SARS-CoV-2 were more similar to those of the less-pathogenic human-specific CoVs. To further investigate adaptive evolution within SARS-CoV-2, we examined codon usage patterns in 3573 genomes of SARS-CoV-2 collected over the initial 4 months of the pandemic. We showed that the ENC values and the CAI values of SARS-CoV-2 were decreasing over the period. The low ENC and CAI values could be responsible for the lower pathogenicity of SARS-CoV-2. While mutational pressure appears to shape codon adaptation in the overall genomes of SARS-CoV-2 and other zoonotic CoVs, the E gene of SARS-CoV-2, which has the highest codon usage bias, appears to be under strong natural selection. Data from the study contribute to our understanding of the pathogenicity and evolution of SARS-CoV-2 in humans.